Antimicrobial bioassay-guided fractionation of a methanol extract of Eupatorium triplinerve. (27th November 2014) - Matos Lopes, Tamyris Regina; de Oliveira, Fábio Rodrigues; Malheiros, Flávia Filocreão; de Andrade, Marcieni Ataíde; Monteiro, Marta Chagas; Baetas Gonçalves, Ana Cristina
Abstract: Context: Eupatorium triplinerve Vahl (Asteraceae), popularly known as Japana, is widely used in folk medicine, due its analgesic, anticoagulant, antianorexic, antiparasitic, anthelmintic, sedative, antifungal, and antibacterial properties. Objective : The present study evaluated the chemical composition and antimicrobial activity of E. triplinerve extracts from different parts of the plant and identified the extract with the highest antimicrobial potential. Materials and methods : Extracts were obtained by maceration of all parts of plant, and subjected to bioassay-guided fractionation of methanol extract by partition column chromatography. The major chemical groups, saponins, reducing sugars, alkaloids, steroids, triterpenoids, phenols, tannins, flavonoids, and others were screened by standard techniques. The antimicrobial activity of the different extracts was performed by microdilution assay and the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were reported. Results : Phytochemical screening of hydroalcoholic extract from all parts of E. triplinerve identified mainly steroids, coumarins, alkaloids, saponins, tannins, depsides and absence of polysaccharides and flavonoids. The methanol extract of leaves presented the highest content of coumarins and lower MIC values of 62 and 75 µg/mL against Enterococcus faecalis and Staphylococcus aureus, respectively. In addition, its non-polar fractions showed antimicrobial activity with MIC ranging from 16 to 125 µg/mL against Gram-negative bacteria, mainly Escherichia coli . Discussion and conclusion : Data showed that non-polar fractions of E. triplinerve methanolic extract has better antimicrobial activity and most likely depends on the presence of several compounds, such as depsidones, coumarins, saponins, and triterpenes on crude extract. The results can be exploited largely in research of new antibacterial agents.